Charakterystyka miejsc gniazdowania jerzyka Apus apus w lasach Roztocza i Równiny Biłgorajskiej - Stachyra, Przemysław; Mysłajek, Robert (Leśne Prace Badawcze, 2022)
During field studies conducted in 2019–2021, the common swift Apus apus was recorded in 78 sites located in the Roztocze and Biłgoraj Plains in south-eastern Poland. In total, 39.3% of the recorded sites were situated in national parks or nature reserves. The number of nesting pairs averaged 1.7 ±0.9 SD (range 1–5) at each study site, and did not differ between protected and managed forests. Swifts occurred in both coniferous and deciduous forests with the majority in old-growth stands (mean 147 years ±28 SD, range 80– 99). Interestingly, the mean stand age favored by the species was significantly higher in the Roztocze National Park (mean 161.9 years ±20.1 SD, range 120–90) than in managed forests (mean 139.4 years ±28.6 SD, range 80–199). All cavities in which swifts nested ( n =28) were located in Scots pines Pinus sylvestris L. with a mean diameter at breast height of 57.5 cm ±9.0 SD (range 40–75 cm), and a mean height of 27.7 m ±3.0 SD (range 23–32 m). Cavities were located between 5 m and 27 m above ground (mean 16.5 m ±5.7 SD). In total, 75% of the cavities inhabited by swifts were excavated by great spotted woodpeckers Dendrocopos major , while the remaining cavities were created through bloating at the site where branches had broken off. These results indicate that in order to protect the relict forest populations of the common swift, it is necessary to preserve patches of old-growth stands.